Encyclopedia of Radiation Oncology - Brady, Luther W.; Yaeger, Theodore E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This comprehensive encyclopedia, comprising a wide range of entries written by leading experts, provides detailed information on radiation oncology, including the most recent developments in the field. It will be of particular value for basic and clinical scientists in academia, practice, and industry and will also be of benefit to those in related fields, students, teachers, and interested laypersons.
SECTION I: SCIENTIFIC FOUNDATIONS OF RADIATION ONCOLOGY -- Part A: Radiobiology -- Part B: Physics -- SECTION II: Techniques and Modalities -- SECTION III: DISEASE SITES -- Part A: Central Nervous System Tumors Overview -- Part B: Head and Neck Tumors Overview -- Part C: Thoracic Neoplams Overview -- Part D: Gastrointestinal Tumors Overview -- Part E: Genitourinary Tumors Overview -- Part F: Gynecologic Tumors Overview -- Part G: Breast Cancer Overview -- Part H: Sarcoma and Benign Disease -- Part I: Childhood Cancers Overview -- Part J: Lymphoma & Hematologic Malignancies Overview.
Keywords: Medicine; Radiology, Medical; Radiotherapy; Oncology; Medicine & Public Health; Radiotherapy; Imaging / Radiology; Oncology